KONSENSUS SEBAGAI PILAR UTAMA GOOD GOVERNANCE DALAM PENGELOLAAN TANAH ULAYAT DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU (Consensus as the Main Pillar of Good Governance in Managing Tanah Ulayat in the Regency of Kuantan Singingi Riau Province) - Agus Mandar; Purwo Santoso; Josef Riwu Kaho (Pusat Studi Lingkungan Hidup Universitas Gadjah Mada, 2004)
ABSTRAKSalah satu persoalan penting pembangunan di Kabupaten Kuantan Singingi adalah konflik dalam pengelolaan tanah ulayat. Terjadi paling tidak 15 kasus konflik yang melibatkan masyarakat lokal dan perusahaan di kabupaten ini. Berdasarkan hasil penyelesaian konflik terdapat 3 katagori penyelesaian yakni: penyelesaian kasus yang penuh, penyelesaian semu, dan tanpa penyelesaian. Penelitian ini bertujuan mengkaji mekanisme penyelesaian konflik tanah ulayat. Melalui teori good governance penelitian ini mengkaji mekanisme penyelesaian konflik prinsip-prinsip good governance dicobakaitkan dengan nilai-nilai lokal. Penelitian ini menemukan bahwa apabila prinsip-prinsip good governance diterapkan dengan mempertimbangkan nilai-nilai budaya lokal, maka konflik-konflik tersebut dapat diselesaikan. ABSTRACTOne of the most well-known and crucial problems in the Regency of Kuantan Singingi development is the conflict in managing tanah ulayat. There are fifteen cases in which conflicts may take place among the local community and the private companies running the land in the Regency. These cases have been categorized into three. There are no consensus cases artificial consensus cases, and truly consensus case. In the analysis process, the researcher has applied theories and the concepts of Local Good Governance. The Good Governance, which can be applied universally, was convergent and applied in a way suitable with the local community traditions in the Kuantan Singingi. This research has proven that the determinant factor of problem solving is the cooperation between the involved polities (the Local Government, Private Companies, and Local Community) in the interaction of tanah ulayat management. The consensus can be achieved when the Local Government is able to establish to Good Governance, the private companies is operating Good Corporate Governance paradigm, which arises through the process of crafting the local community’s culture, based on the local customs heritages.